Student perceptions and use of feedback during active learning: a new model from repeated stimulated recall interviews. Issue 3 (3rd April 2019) - Wiltbank, Lisa; Williams, Kurt; Salter, Rachel; Marciniak, Lauren; Sederstrom, Emily; McConnell, Melody; Offerdahl, Erika; Boyer, Jeffrey; Momsen, Jennifer
Abstract: As active learning pedagogies continue to increase in popularity in higher education, new questions have emerged about how instructors can manage all of the associated 'moving parts' of active learning, including how and when to deliver feedback. Currently, little is known about how students perceive the effects of verbal feedback during in-class activities. This study examined two large sections of introductory biology held in an active learning SCALE-UP (Student-Centred Active Learning Environments with Upside-down Pedagogies) classroom. Thematic analysis of repeated stimulated recall interviews with 15 students (72 total interviews) uncovered three main categories of feedback effects that students perceived: assure, alert and add (AAA). These three categories were supported by repeated stimulated recall surveys with a larger student population (262 students). We describe each category, quantify the frequency of each category in the target course, outline the students' perceived impact of each on examination preparation and performance, and conclude with implications regarding how understanding students' perceptions of their feedback experience may help instructors to deliver student-centred feedback during active learning.